Peningkatan Kemampuan Berpikir Kreatif dan Komunikasi Matematis Siswa SMA melalui Model Pembelajaran Project Based Learning Berbasis Debat - Tien Fitrina; M. Ikhsan; Said Munzir (Didaktik Matematika, 2016)
The purpose of this study was to determine between increased ability to think creatively and mathematical communication students who take the learning project-based learning and students who received conventional learning. The research sample was taken randomly. The instrument used was a test form of essay questions given in pretest and posttest to see an increase, as well as about the student activity sheet that would be a reference in the debate. Based on statistical data analysis using t-test showed that the increase in the ability to think creatively and communication students acquire mathematical learning project-based learning was better than students who received conventional learning. Based on the analysis statistical data by using the Two-Way ANOVA showed that there was no interaction between the model of learning by the student's ability level to increase the ability of creative thinking and mathematical communication students